Tax Compliance in the Perspective of Motivation Theory X and Y and Their Implications for Fraud - Dedi Kurniawan; Sahat Parlindungan Hutapea; Erza Rahmi Andini; Rizki Lanniari HS (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2022)
Indonesia applies the principle of a self-assessment system in its tax collection process. The public is expected to comply with this rule by calculating, depositing, and self-reporting the tax they owe. Therefore, the level of public awareness of taxes is a major factor in the operation of this system. However, in reality, there are still many people who intentionally or unintentionally commit tax fraud. So, the tax collection process does not run as effectively as expected. This study was conducted to determine the effect of knowledge on tax benefits and sanctions on tax compliance. The research was conducted in the Batam State Polytechnic campus and industry. The object of this research is students and employees who already have the obligation to pay taxes. The research was conducted by combining two methods, namely, experimental and case studies. This method examines the causal relationship between the independent variable and the dependent variable and explores employee tax compliance. Based on the results of data collection, processing, and analysis, it is obtained that people have a high motivation to comply with taxes if they know the benefits of paying taxes.